2018
DOI: 10.1371/journal.pone.0194235
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic dysfunction in whiplash associated disorders: A systematic review

Abstract: BackgroundResearch investigating Whiplash Associated Disorder (WAD) has largely focused on the cervical spine yet symptoms can be widespread. Thoracic spine pain prevalence is reported ~66%; perhaps unsurprising given the forceful stretch/eccentric loading of posterior structures of the spine, and the thoracic spine’s contribution to neck mobility/function. Approximately 50% WAD patients develop chronic pain and disability resulting in high levels of societal and healthcare costs. It is time to look beyond the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…In accordance with the protocol [22] meta-analyses would be performed where a sufficient number of studies share all of the stated characteristics; design, measure of dysfunction, severity based on QTF and stage post whiplash injury.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…In accordance with the protocol [22] meta-analyses would be performed where a sufficient number of studies share all of the stated characteristics; design, measure of dysfunction, severity based on QTF and stage post whiplash injury.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…We also combined pain in the cervical and thoracic regions as they often accompany each other [ 1 , 5 ]. Thoracic pain and dysfunction is also common in many cervical disorders [ 45 ]. The movement control tests in this study have shown adequate (moderate to almost perfect) inter-rater agreement but lower (fair to substantial) test-retest agreement, which should be considered in follow-up situations [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise has shown to be a useful approach in 50 to 90% of all TOS cases [ 6 ]. Although there is much variation within and between individuals, symptoms of TOS generally improve with exercise and other physical therapy techniques (e.g., manual therapy or manual adjustments) [ 21 , 60 , 61 , 62 , 63 ]. In a general exercise session, emphasis on proper scapular function during upper-body movements, breathing techniques, and head and pelvis alignment during various tasks is essential for treating TOS [ 36 , 58 , 64 ].…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Repeated trauma to the head or neck, postural dysfunction, extended duration in compromising shoulder positions, pregnancy, edema, anatomical deviations, hypertrophied muscles (e.g., scalenes), boney growths, and muscle weakness are all theorized to be contributing factors to TOS [ 2 , 4 , 9 , 11 , 12 , 13 , 18 ]. The most commonly presented cause of TOS appears to be an abrupt flexion-extension motion (e.g., whiplash) at the atlantoaxial joint and other joints between the cervical vertebrae, which can lead to symptoms present with both vTOS and nTOS [ 2 , 9 , 16 , 21 ]. This whiplash motion can result in instability at the atlantoaxial joint, causing the surrounding musculature to shorten, in order to compensate for the laxity in the joint.…”
Section: Introductionmentioning
confidence: 99%